Netizen Politeness Strategies in the Instagram Comment Section of Kraton Kasunanan Surakarta Pakubuwana - Setyawardana, Ardi; Musfiroh, Tadkiroatun; Nurbaya, St. (International Journal of Language Teaching and Education, 2026)
This study investigates netizen politeness strategies in the Instagram comment section of @kraton_solo (Kraton Kasunanan Surakarta Pakubuwana) from September 2025 to March 2026, a period shaped by the death of Pakubuwana XIII and an ensuing succession conflict. Grounded in a sociopragmatic framework that integrates Brown and Levinson’s (1987) politeness taxonomy as the primary analytical tool and Leech’s (1983) politeness maxims as a complementary value-orientation framework, this qualitative descriptive study analyzed 44 purposively selected comments to reach theoretical saturation. Findings show that off-record and positive politeness strategies were equally prominent (31.8% each), followed by bald-on-record (20.5%) and negative politeness (15.9%). The prominent use of off-record strategies reflects the Javanese cultural tradition of indirect expression (sasmita and sanepa) operating in digital contexts as acceptable vehicles for critique. Meanwhile, the persistence of krama inggil in positive politeness demonstrates that the Javanese unggah-ungguh register system adapts to, rather than erodes in, digital communication by hybridizing with markers such as emojis. Ultimately, these findings contribute to the development of sociopragmatics by demonstrating how universal frameworks can accommodate digitally mediated Javanese cultural nuances, offering practical insights into netizen communication dynamics on sensitive socio-cultural issues.